EFFECT OF BIO FERTILIZER ON MATURE OIL PALM IN NORTH SUMATRA AND RIAU - Y Taryo Adiwiganda; Balaman Tarigan; Berani Purba (Indonesian Journal of Agricultural Science, 2006)
Chemical fertilizers have routinely been applied at oil palm plantations to maintain soil fertility. Due to the increase of chemical fertilizer prices, some efforts have been done at such as to reduce cost and increase efficiency in chemical fertilizer application at oil palm plantations include the use of bio fertilizer (BF). The objective of experiment was to evaluate the effect of reducing oil palm standard dosage of chemical fertilizers combined with BF on mature oil palm yield. The experiment was carried out in 2002-2003 covering an area of 4367 ha at PTPN IV in North Sumatra and of 515.58 ha at PTPN V in Riau. The planting material was Dura x Pasifera variety and planted in 1980-1995. A randomized block design was used having three fertilizer treatments: (A) 100% chemical fertilizer (normal dosage), (B) 75% chemical fertilizer + BF, and (C) 50% chemical fertilizer + BF. The replications at PTPN IV and V were 11 and 7, respectively. The BF was applied firstly in May 2002. Dosage of BF was 250 g tree-1 yr-1. The BF was given in pockets with four pockets per palm tree. The parameters observed were fresh fruit bunch (FFB) weight, average of bunch weight, and average of bunch number. Results of the experiments showed that palm yield treated with 75% chemical fertilizer + BF and 50% chemical fertilizer + BF were both not significantly different with palm yield treated with 100% chemical fertilizer. The application of 75% chemical fertilizer + BF and 50% chemical fertilizer + BF gave benefit of Rp509,093 and Rp1,231,535 ha-1 yr-1, respectively. Technically, nutrients given as chemical fertilizers using combination of 75% chemical fertilizer + BF are still higher than the nutrients transported into 26 tons palm FFB ha-1 yr-1. Fertilizer treatment combination of 50% chemical fertilizer + BF will technically be safe only for palm yield of <16 tons palm FFB ha-1 yr-1, since nutrients given as fertilizer are still higher than those transported into the palm yield.